2005
DOI: 10.1101/lm.89305
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of rat hippocampal LTP by holeboard training

Abstract: Hippocampal long-term potentiation (LTP) can be dissociated in early-LTP lasting 4-5 h and late-LTP with a duration of more than 8 h, the latter of which requires protein synthesis and heterosynaptic activity during its induction. Previous studies in vivo have shown that early-LTP in the dentate gyrus can protein synthesis-dependently be transformed (reinforced) into late-LTP by the association of arousing novel environmental stimuli. Here we show that consolidation of spatial memory also reinforces early-LTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 69 publications
(70 reference statements)
5
58
0
1
Order By: Relevance
“…Third, the induction of inhibitory avoidance-LTM formation by spatial novelty was blocked by delivering the protein synthesis inhibitor anisomycin into the CA1 region immediately after the exposure to a novel environment. Frey and colleagues (Straube et al, 2003b;Uzakov et al, 2005) have previously found that novelty-and holeboard training-induced LTP reinforcement in the hippocampus, is dependent on new protein synthesis. Indeed, we demonstrated that the amnesia induced by blockade of protein synthesis immediately before strong inhibitory avoidance training was rescued by a previous exposure to novelty.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the induction of inhibitory avoidance-LTM formation by spatial novelty was blocked by delivering the protein synthesis inhibitor anisomycin into the CA1 region immediately after the exposure to a novel environment. Frey and colleagues (Straube et al, 2003b;Uzakov et al, 2005) have previously found that novelty-and holeboard training-induced LTP reinforcement in the hippocampus, is dependent on new protein synthesis. Indeed, we demonstrated that the amnesia induced by blockade of protein synthesis immediately before strong inhibitory avoidance training was rescued by a previous exposure to novelty.…”
Section: Discussionmentioning
confidence: 99%
“…4 D) (Bonferroni's test; p Ïœ 0.001). This experiment demonstrates a relationship between gamma oscillatory activity and the metaplasticity of synaptic strength in visual cortex Discussion LTP and LTD may be involved intrinsically in memory processing (ManahanVaughan and Braunewell, 1999;Kemp and Manahan-Vaughan, 2004, 2005Uzakov et al, 2005;Whitlock et al, 2006). Apart from its role in development, the visual cortex has been proposed as a memory system, involved in encoding stimulus features and in the short-term storage of sensory stimuli to guide behavior (Pasternak and Greenlee, 2005).…”
Section: Circadian-dependent Activity States Drive Bidirectional Synamentioning
confidence: 99%
“…In their seminal work they showed that early-LTP, a transient form of LTP that is induced by a weak stimulus, could be extended to late-LTP, a more persistent form of LTP, if the weak and the strong stimuli were applied in a relatively long-lasting associative time window on different synapses of the same neuron. Frey and colleagues also found that an hippocampal LTP can be reinforced by exposing rats to a novelty or to a holeboard training and this phenomenon is protein synthesisdependent (10,11).…”
mentioning
confidence: 99%
“…In their seminal work they showed that early-LTP, a transient form of LTP that is induced by a weak stimulus, could be extended to late-LTP, a more persistent form of LTP, if the weak and the strong stimuli were applied in a relatively long-lasting associative time window on different synapses of the same neuron. Frey and colleagues also found that an hippocampal LTP can be reinforced by exposing rats to a novelty or to a holeboard training and this phenomenon is protein synthesisdependent (10,11).Considering that LTP and some forms of LTM share a number of properties, such as associativity, durability and protein synthesis dependence (12), it is feasible that a mechanism of STC, also operates in the formation of LTM.The main goal of the present work is to study the process of behavioral tagging using several combinations of behavioral tasks, to investigate whether a behavioral experience can extend the duration of the memory for an independent task by providing the PRPs needed for its consolidation. We found that the behavioral tagging process operates in different hippocampus-and cerebral cortex-dependent learning tasks, suggesting that it represents a general mechanism of LTM formation.…”
mentioning
confidence: 99%